(untitled) (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we consider the three-dimensional generalized Navier-Stokes equation with a nonlinear damping term |u|^β−1 (β ≥ 1). Firstly, utilizing the Fourier splitting method, we derive decay estimates for weak solutions to the equations when α = 0 and β = 1, as well as when 0 < α max{ 4α3+1, 2}, we obtain the same result.